A framework for the digital competencies for teaching in science education – DiKoLAN. Issue 1 (1st June 2022) - Thoms, Lars-Jochen; Kremser, Erik; Kotzebue, Lena von; Becker, Sebastian; Thyssen, Christoph; Huwer, Johannes; Bruckermann, Till; Finger, Alexander; Meier, Monique
Abstract: In order to systematically introduce (prospective) teachers to teaching in the digital world and to lay the foundations for concepts that are meaningful in terms of physics education, essential aspects of learning with and via digital media must be conveyed. In addition to cross-curricular competencies, it is essential to consider subject-specific competencies for the natural sciences since the formation of subject-specific knowledge on the use of digital media in the classroom (TPACK) is the decisive factor for acceptance behaviour and the intention for later use. The questions remain as to what core competencies must be built up by all (prospective) science teachers by the end of their studies and in which sections of university teacher training this should take place. Since no competence frameworks specific to the teaching of science were previously available, nine researchers from eight universities came together to develop a suitable orientation framework. As a result, this contribution presents the structured and graded framework "DiKoLAN – Digitale Kompetenzen für das Lehramt in den Naturwissenschaften [Digital Competencies for Teaching in Science Education]" (see https://dikolan.de).